Prognostic Value of Quantative EEG Prior to Electroconvulsive Therapy in Psychotic Disorders and Major Depression (Annals of Medical Research, 2021)
Aim: There is no consensus between different clinics about the usage of remaining blood in venous reservoir during coronary bypass surgery with cardiopulmonary bypass operation. Our prospective study, we aimed to research effects of the use of remaining
Keywords: Quantitative EEG; Electroconvulsive Therapy; Fourier Analysis.